Timun Mas “Melestarikan Budaya Lewat Cerita Rakyat” - Hanan Khanafi; Rendy Ray Ismahendra; Rizqi Ishal Wibisono; Rayhan Bimantoro; Firstania Maydina Brillianty; Ayu Aliviana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Efforts to increase interest in reading and to preserve culture, especially traditional culture, which is increasingly marginalized day by day. need to reintroduce good moral values ​​for children. Therefore, the folklore of Timun Mas has content and benefits in instilling moral values ​​in life to determine whether an action is good or not in everyday life. The character values ​​in the folk tale "Timun Mas" are religious, honest, disciplined, hard working, creative, independent, curious, communicative, peace-loving and responsible. With these character values, this story can be an example for readers, especially children who really like stories as bedtime stories.